30.8k views
0 votes
What is the completely factored form of f(x)=x^3+4x^2+7x+6?

f(x)=(x+2)(x−(−3+i10−−√))(x−(−3−i10−−√))
f(x)=(x+2)(x−(−1+i2√))(x−(−1−i2√)) f(x)=(x−2)(x−(−1+i2√))(x−(−1−i2√))
f(x)=(x−2)(x−(−3+i10−−√))(x−(−3−i10−−√))

User Chol Nhial
by
4.7k points

1 Answer

4 votes

we are given


f(x)=x^3+4x^2+7x+6

We will use rational root theorem to find factors

We can see that

Leading coefficient =1

constant term is 6

so, we will find all possible factors of 6


6=\pm 1,\pm 2,\pm 3,\pm 6

now, we will check each terms

At x=-2:

We can use synthetic division

we get


f(-2)=0

so, x+2 will be factor

and we can write our expression from synthetic division as


f(x)=x^3+4x^2+7x+6=(x+2)(x^2+2x+3)


f(x)=(x+2)(x^2+2x+3)

now, we can find factor of remaining terms


x^2+2x+3=0

we can use quadratic formula


\mathrm{For\:a\:quadratic\:equation\:of\:the\:form\:}ax^2+bx+c=0\mathrm{\:the\:solutions\:are\:}


x=(-b\pm √(b^2-4ac))/(2a)

we can compare our equation with quadratic equation

we get


a=1,b=2,c=3

now, we can plug these values


x=(-2+√(2^2-4\cdot \:1\cdot \:3))/(2\cdot \:1)


x=-1+√(2)i


x=(-2-√(2^2-4\cdot \:1\cdot \:3))/(2\cdot \:1)


x=-1-√(2)i

so, we get


x=-1+√(2)i,\:x=-1-√(2)i

so, we can write factor as


x^2+2x+3=(x-(-1+√(2)i))(x-(-1-√(2)i))

so, we get completely factored form as


f(x)=(x+2)(x-(-1+√(2)i))(x-(-1-√(2)i))...............Answer


What is the completely factored form of f(x)=x^3+4x^2+7x+6? f(x)=(x+2)(x−(−3+i10−−√))(x-example-1
User Grunge Fightr
by
5.7k points